2014
DOI: 10.1016/j.cub.2014.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Integrin-Associated Complexes Form Hierarchically with Variable Stoichiometry in Nascent Adhesions

Abstract: Summary Background A complex network of putative molecular interactions underlies the architecture and function of cell-matrix adhesions. Most of these interactions are implicated from co-immunoprecipitation studies using expressed components; but few have been demonstrated or characterized functionally in living cells. Results We introduce fluorescence fluctuation methods to determine, at high spatial and temporal resolution, ‘when’ and ‘where’ molecular complexes form and their stoichiometry in nascent ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
131
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(150 citation statements)
references
References 56 publications
(90 reference statements)
12
131
0
Order By: Relevance
“…Therefore integrins, and β1-containing integrins in particular, are necessary for haptotaxis but are not differentially localized. Kindlins and talin activate integrins, and kindlin2 has been shown to associate with β1 integrin at nascent adhesions before talin recruitment during adhesion maturation (Bachir et al, 2014). Consistent with a central role of β1-containing integrins, depletion of kindlin2 in fibroblasts (Fig.…”
Section: Differential Lamellipodial Protrusion Dynamics Regulate Haptmentioning
confidence: 59%
“…Therefore integrins, and β1-containing integrins in particular, are necessary for haptotaxis but are not differentially localized. Kindlins and talin activate integrins, and kindlin2 has been shown to associate with β1 integrin at nascent adhesions before talin recruitment during adhesion maturation (Bachir et al, 2014). Consistent with a central role of β1-containing integrins, depletion of kindlin2 in fibroblasts (Fig.…”
Section: Differential Lamellipodial Protrusion Dynamics Regulate Haptmentioning
confidence: 59%
“…Thus, when the pentameric fibronectin type III domain 7-10 was used as a ligand, it supported 6-to 9-fold greater force per fibronectin than the corresponding monomeric form (10). The formation of early integrin clusters typically occurs at the cell edge, when the membrane protrudes forward and encounters new matrix, and involves talin and/or kindlin binding (11)(12)(13). After the initial clusters form, some grow into mature adhesions in a myosin-II-dependent manner (14)(15)(16)(17).…”
Section: Integrin Clustering: Minimal Adhesion Unitmentioning
confidence: 98%
“…In this mode, integrin α5β1, kindlin2, talin-1 and vinculin enter nascent adhesions simultaneously. However, cross-variance analysis has revealed that, during adhesion assembly, α5β1 is bound to kindlin2, and talin bound to vinculin; however, these two subcomplexes are not bound to each other until the nascent adhesion becomes stabilised by myosin II activity (Bachir et al, 2014). Thus, talin can be retained at the adhesion without maintaining integrin binding, and interactions between IAPs can change following recruitment.…”
Section: Recruitment Of Talin To Integrin Adhesion Sitesmentioning
confidence: 99%
“…1, where talin dimers are recruited by binding to a ligand-bound integrin, and then can insideout activate integrins that diffuse within suitable proximity. However, examination of nascent adhesions in epithelial cells revealed a third mode of initial recruitment (Bachir et al, 2014). In this mode, integrin α5β1, kindlin2, talin-1 and vinculin enter nascent adhesions simultaneously.…”
Section: Recruitment Of Talin To Integrin Adhesion Sitesmentioning
confidence: 99%